Immunological methods in diagnosis of sarcoidosis end tuberculosis of lung - M. А. Belokurov; A. А. Starshinova; V. Yu. Zhuravlev; L. D. Kiruchina; М. V. Pavlova; I. V. Chernokhaeva; L. I. Archakova; A. R. Kozak; V. A. Tsinzerling; P. K. Yablonskii (Журнал инфектологии, 2015)
Differential diagnosis disseminated diseases provides sarcoidosis and tuberculosis. Frequency of mistakes consists over 40% [Visel AA, 2013]. That’s why including of new diagnosis methods is weary important. Оbjective: to indicat diagnosis value of immunologic methods in differential diagnosis with sarcoidosis and tuberculosis. In the department of phthisiopulmonology were examined 66 patients with lung over 2013 to 2014. Complex of examination included: examination of the respiratory excretion material (sputum) for detection of MBT using laboratory methods, X-ray examination (computed tomography), histological examination after transbronchial biopsy of lung tissue. All of diagnosis were proved by histological and bacteriological methods. After complex of examination patients were divided in two groups: I group (n=32) – pulmonary TB; II group (n=17) – sarcoidosis II study. All of patients were examined with immunologic tests (tuberculin skin test (TST), Diaskintest® (DST) QuantiFERON ®-TB Gold (QFT) and T.-SPOT.TB test (T-SPOT). In the I group this tests was significant different positive results with QFT (78,1%), T-SPOT (71,9%), DST (81,3%) in comparison with negative results of this tests (p˂0,001). Diagnostic value was: TST (DSe – 84,4%, DSp – 40,0%, Dv – 70,2%, PVPR – 75,0%, PVNR – 54,5%); QFT (DSe – 74,2%, DSp – 88,2%, Dv – 79,2%, PVPR – 92,0%, PVNR – 65,2%); TB.SPOT (DSe – 80,6%, DSp – 87,5%, Dv – 83,0%, PVPR – 92,6%, PVNR – 70,0%); DST (DSe – 81,3%, DSp – 94,1%, Dv – 85,7%, PVPR – 96,3%, PVNR – 72,7%); Сonclusion: diagnostic value of immunologic tests QFT, TB.SPOT and DST was more significantly higher in comparison with TST. The use of immunological tests can help in differential diagnosis of tuberculosis and sarcoidosis.